1.a)x=1
b) x=1
c) x=2.5
d) x= -23/33
e) x=-0.625
f) x=-0.75
2. 7.5
Пошаговое объяснение:
1.a) (3x+5)+(8x+1)=17
3x+5+8x+1=17
3x+8x=17-5-1
11x=11
x=1
b)19-5(3x-1)=9
19-15x+5=9
-15x=9-19-5
-15x=-15
c)30+5(3x-1)=35x-25
30+15x-5=35x-25
15x-35x=-25-30+5
-20x=-50
x=2.5
d)10x-5=6(8x+3)-5x
10x-5=48x+18-5x
10x-48x+5x=18+5
-33x=23
x= -23/33
e)6(8x+5)=0
48x+30=0
48x=-30
x=-0.625
f)6(8x+5)=-6
48x+30=-6
48x=-6-30
48x=-36
x=-0.75
2. 4(5-3a)+5(3a-4) при a=2.5
20-12a+15a-20
20 и -20 сокращаются
-12a+15a=-12*2.5+15*2.5=2.5(-12+15)=2.5*3=7.5
1.a)x=1
b) x=1
c) x=2.5
d) x= -23/33
e) x=-0.625
f) x=-0.75
2. 7.5
Пошаговое объяснение:
1.a) (3x+5)+(8x+1)=17
3x+5+8x+1=17
3x+8x=17-5-1
11x=11
x=1
b)19-5(3x-1)=9
19-15x+5=9
-15x=9-19-5
-15x=-15
x=1
c)30+5(3x-1)=35x-25
30+15x-5=35x-25
15x-35x=-25-30+5
-20x=-50
x=2.5
d)10x-5=6(8x+3)-5x
10x-5=48x+18-5x
10x-48x+5x=18+5
-33x=23
x= -23/33
e)6(8x+5)=0
48x+30=0
48x=-30
x=-0.625
f)6(8x+5)=-6
48x+30=-6
48x=-6-30
48x=-36
x=-0.75
2. 4(5-3a)+5(3a-4) при a=2.5
20-12a+15a-20
20 и -20 сокращаются
-12a+15a=-12*2.5+15*2.5=2.5(-12+15)=2.5*3=7.5